2017
DOI: 10.1080/00016489.2017.1378435
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pure-tone audiogram findings and speech perception among older Japanese persons

Abstract: The PTT on the pure-tone audiogram (PTA) is a good predictor of SP by speech audiometry among older persons, which could provide clinically important information for hearing aid fitting and cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…However, the variability of speech recognition performance has increased greatly in patients with moderate and severe hearing loss, with the greatest variability occurring when the 4FPTA falls within the range of 60 to 80 dB HL. This trend in tonal mandarian-speaking patients is consistent with those reported by Hoppe et al and Maeda et al [11,12]. As a result, 4FPTA cannot accurately re ect an individual's speech recognition ability.…”
Section: Resultssupporting
confidence: 89%
“…However, the variability of speech recognition performance has increased greatly in patients with moderate and severe hearing loss, with the greatest variability occurring when the 4FPTA falls within the range of 60 to 80 dB HL. This trend in tonal mandarian-speaking patients is consistent with those reported by Hoppe et al and Maeda et al [11,12]. As a result, 4FPTA cannot accurately re ect an individual's speech recognition ability.…”
Section: Resultssupporting
confidence: 89%
“…The wide use of PTA as a general indicator of hearing loss (e.g., for participant inclusion in audiology studies) can be explained by the simplicity of this measure and the fact that threshold elevation is a robust predictor for unaided speech comprehension in HI people. In correlational studies, audiometric sensitivity typically explains 50-75% of the variance in intelligibility measures across listeners in various tasks 1 (Festen and Plomp, 1983;van Rooij and Plomp, 1990;George et al, 2007;Houtgast and Festen, 2008;Sheft et al, 2012;Humes, 2013;Maeda et al, 2018). For instance, Humes (2007) reports a strong dependency between the (highfrequency) PTA of 24 unaided HI listeners and their wordrecognition scores measured in quiet and against a steady speechshaped noise (both R 2 > 65%).…”
Section: Age-related and Audibility-related Deficits In Presbycusismentioning
confidence: 99%
“…Although the association between speech perception in silence and high-frequency thresholds in pure-tone audiometry has not been reported in cochlear-implanted patients, previous reports showed the association of speech perception in non-implanted patients with hearing loss, especially at high frequencies (15,18). Another study, in non-implanted patients, showed the importance of preservation of the extended high frequencies (>8,000 Hz) and the performance in noise (19).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, preservation of low-frequency auditory hearing is associated with better speech perception after cochlear implantation (14). However, in non-implanted patients, a deterioration of the speech perception is associated with an impairment of the mid and high-frequency thresholds (15).…”
Section: Introductionmentioning
confidence: 99%